Pendekatan Isolasi Fungi Endofit untuk Mendukung Penemuan Obat Berbasis Mikroorganisme - elfira jumrah (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Endophytic fungi are microorganisms that inhabit healthy plant tissues without causing disease symptoms and represent a promising source of bioactive secondary metabolites for drug discovery. This review evaluates current approaches to endophytic fungal isolation and their implications for microorganism-based drug development. A systematic literature search was conducted across Scopus, Web of Science, PubMed, ScienceDirect, and Google Scholar for publications from 2014–2024. Of 6,583 identified articles, 257 met the inclusion criteria and were analyzed. The review found that surface sterilization using 70% ethanol combined with 2–3% sodium hypochlorite is the most effective and widely adopted protocol. The use of diverse culture media (PDA, MEA, and CDA) enhances isolate diversity, while molecular identification based on ITS-rDNA, supported by LSU, β-tubulin, and TEF1-α markers, provides reliable taxonomic resolution. Furthermore, integrating culture-dependent methods with high-throughput metagenomic sequencing expands access to previously unculturable endophytic fungi. Optimized and standardized isolation protocols, together with omics technologies, are essential for maximizing the potential of endophytic fungi as a sustainable source of novel bioactive compounds and future therapeutic agents.